Biological activity of rhizobacteria isolated from rhizosphere Acacia crassicarpa A. Cunn ex Benth. in timber plantations - Zul, D.; Mustava, M.; Diva, A. R.; Siregar, B. A.; Gafur, A.; Tjahjono, B. (International Journal of Agricultural Technology, 2022)
Acacia crassicarpa is widely planted in timber plantations for pulp and paper industry. However, A. crassicarpa is relatively susceptible to diseases. To control diseases and promote the growth of A. crassicarpa, one of the efforts is utilized rhizobacteria or is known as plant growth-promoting rhizobacteria (PGPR). The biological activity of 27 isolates from the rhizosphere of A. crassicarpa was explored the ability of isolates to produce siderophores, hydrogen cyanide (HCN), indole acetic acid (IAA), and antagonism assays. The ability of isolates to produce siderophores and HCN was determined qualitatively by inoculation of the isolates on iron-free chrome azurol S agar and King’s B medium, respectively. IAA production was estimated colorimetrically by culturing the isolate on nutrient broth containing L-tryptophan as a precursor. The characteristic of the isolates capable of producing IAA is the color change of the culture after the addition of Salkowski’s reagent. Antagonisms assay on pathogens that cause leaf blight and wilt were performed by using a cross-streaking method and dual culture method, respectively. It was found that 23 isolates showed the ability to produce siderophores as indicated by the formation of orange halo around colonies. According to the color change of the filter paper to light brown and dark brown, five isolates were found to produce weak and moderate HCN. Seven isolates produced IAA with a concentration in the range of 108.07-73.78 ppm. Isolate 010B performed the best ability to inhibit the growth of Fusarium sp. (61.10%) and Xanthomonas sp. (28.14%). The study results it can be concluded that there were two isolates with potential as biocontrol and growth promoter agents